2020
DOI: 10.1108/k-04-2020-0228
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employee participation in online innovation communities on idea quality

Abstract: Purpose Online user innovation community (OUIC) has become a vital source for enterprises to obtain user innovation ideas and interact with users in new product development. However, most studies only focus on the relationship between users and ideas, often ignoring the influence of employees in the innovation platform. The purpose of this study is to explore the impact of employee behaviors on idea quality in OUIC. Design/methodology/approach In this paper, the authors collected sample data of open user inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…As a popular application, open innovation community has received attention from information systems researchers. Open innovation community reflects a platform that enables users to share their innovative ideas on product and services with enterprises, which can adopt these ideas into the research and development processes and improve the products and services (Yu and Liu, 2021). Thus, users' contribution, which means their posting, commenting and updating of innovative ideas, is crucial to the success of open innovation communities (Ma et al, 2019) semiconductor industry and found that virtual brand communities can be used to implement open innovation.…”
Section: Open Innovation Community User Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…As a popular application, open innovation community has received attention from information systems researchers. Open innovation community reflects a platform that enables users to share their innovative ideas on product and services with enterprises, which can adopt these ideas into the research and development processes and improve the products and services (Yu and Liu, 2021). Thus, users' contribution, which means their posting, commenting and updating of innovative ideas, is crucial to the success of open innovation communities (Ma et al, 2019) semiconductor industry and found that virtual brand communities can be used to implement open innovation.…”
Section: Open Innovation Community User Behaviourmentioning
confidence: 99%
“…Zheng et al (2018) noted that creator, project and user participation characteristics affect project success in co-innovation communities. Similarly, Yu and Liu (2021) reported the effect of employee participation on idea quality in innovation communities.…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…Moreover, past comments have the highest effect on idea quality, compared with all the other factors researched. We can thus conclude that constantly participating and gathering experience in ideation platforms is a good approach for users to improve the potential value of their ideas (Yu and Liu, 2020), especially by learning and commenting on others' ideas.…”
Section: Discussion and Future Workmentioning
confidence: 93%
“…The mean score across these criteria was used to measure overall quality. Other scholars, however, hold that an idea ought to be actually implemented by an organization (Bayus, 2013;Beretta, 2019;Liu et al, 2020;Yu and Liu, 2020), which is an objective means to evaluate idea quality (Bayus, 2013). In fact, an idea should be novel, useful and feasible in order to be implemented by a company (Franke et al, 2006;Hwang et al, 2019).…”
Section: Ejim 263mentioning
confidence: 99%
“…First, the study contributes to a stream of research that emphasizes the importance of influencing factors from two previous dimensions. Although prior research has investigated the concept of the quality of creative information, much of that literature only stresses the information or information publishers (Yu and Liu, 2020). This study extends the existing literature and suggests information characteristics, and information publishers characteristics are both critical factors, and then combine the two dimensions exploring how that factor influences the quality of creative information (Shi et al , 2020).…”
Section: Discussionmentioning
confidence: 99%